A Method for Detection of Water Permeation Events in Molecular Dynamics Simulations of Lipid Bilayers - Camilo, Carlos Roberto de Souza [UNESP] (2022)
The cell membrane is one of the most important structures of life. Understanding its functioning is essential for several human knowledge areas, mainly how it controls the efflux of substances between the cytoplasm and the environment. Being a complex structure, composed of several classes of compounds such as lipids, proteins, and sugars, a convenient way to mimic it is through a phospholipid bilayer. Molecular dynamics (MD) simulations of lipid bilayers in solution are the main computational approach to model the cell membrane. The characterization of permeation events through the bilayer provides information about the lipid interaction, and the effects of proteins and other molecules over the bilayer permeability. Due to the fast dynamics, the identification of small molecules permeation can poorly be done in traditional analyzes, such as density profiles. In this work, we present a method to detect water molecules permeation events through the lipid bilayer, characterizing its crossing time and trajectory. By splitting the simulation box into well-defined regions, the method distinguishes the passage of molecules through the bilayer from artifacts produced by crossing molecules through the simulation box edges when using periodic boundary conditions. The method provides an additional tool to analyze equilibrium MD membrane simulations and its computational implementation can be applied to common trajectory files.